2016
DOI: 10.1186/s12918-016-0341-9
|View full text |Cite
|
Sign up to set email alerts
|

Attractor landscape analysis of colorectal tumorigenesis and its reversion

Abstract: BackgroundColorectal cancer arises from the accumulation of genetic mutations that induce dysfunction of intracellular signaling. However, the underlying mechanism of colorectal tumorigenesis driven by genetic mutations remains yet to be elucidated.ResultsTo investigate colorectal tumorigenesis at a system-level, we have reconstructed a large-scale Boolean network model of the human signaling network by integrating previous experimental results on canonical signaling pathways related to proliferation, metastas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 75 publications
2
46
0
Order By: Relevance
“…A variety of network models of cancer cells has been previously established to investigate such dynamic features of the network from a systems biological perspective. However, previous studies have mainly focused on qualitative assessments of cancer such as changes in input-output relationships in cancer cells or comparison of major attractors between normal and cancer cells [19, 40]. For instance, a recent study employed a network modeling approach to identify control targets for anti-cancer treatment by qualitatively examining the changes of basin size between major attractors, such as proliferation and apoptosis [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of network models of cancer cells has been previously established to investigate such dynamic features of the network from a systems biological perspective. However, previous studies have mainly focused on qualitative assessments of cancer such as changes in input-output relationships in cancer cells or comparison of major attractors between normal and cancer cells [19, 40]. For instance, a recent study employed a network modeling approach to identify control targets for anti-cancer treatment by qualitatively examining the changes of basin size between major attractors, such as proliferation and apoptosis [40].…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies have mainly focused on qualitative assessments of cancer such as changes in input-output relationships in cancer cells or comparison of major attractors between normal and cancer cells [19, 40]. For instance, a recent study employed a network modeling approach to identify control targets for anti-cancer treatment by qualitatively examining the changes of basin size between major attractors, such as proliferation and apoptosis [40]. However, these system-based studies still have fundamental limitations in systematic control for cancer reversion because there is no quantitative evaluation of cancer status.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding cancer research, in the last years it has found valuable support in a wide range of modeling and simulation approaches, which cover a wide spectrum ranging from mathematical models -e.g., continuous models [2][3][4] and stochastic models [5][6][7][8] to computational models -e.g., Monte Carlo method and cellular automata [9][10][11], Boolean networks [12], Petri nets [13], artificial neural networks [14][15][16] and expert systems [17]. These approaches have allowed the in silico experimentation in cancer at the cellular, system and patient level.…”
Section: Bodymentioning
confidence: 99%
“…The purpose of the study we propose here is not to provide a comprehensive 60 molecular description of the response but to verify that the existence and functionality of the 61 suggested feedback loops around the signalling pathway in which BRAF is involved [21] may be a 62 first hint towards these differences. For a more thorough study of these cancers, we refer to other 63 works [4,24,25].…”
Section: Introductionmentioning
confidence: 99%